2014
DOI: 10.1007/s13277-014-2651-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma-derived growth factor: a novel prognostic biomarker in intrahepatic cholangiocarcinoma

Abstract: Hepatoma-derived growth factor (HDGF) is an acidic heparin-binding protein involved in tumor progression and poor prognosis of kinds of cancers. Aimed at investigating the functions of HDGF in intrahepatic cholangiocarcinoma (IHCC), we detected the expression of HDGF by immunohistochemistry in 83 patients. Associations of HDGF with clinicopathologic features, microvascular density (MVD), and overall survival rates were further analyzed by Chi-square method, univariate or multivariate analysis. HDGF functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Paraffin-embedded specimens were cut into 5-μm sections, followed by IHC staining with anti-TBL1XR1 (1:400, HPA019182, Sigma), anti-Cyclin-D1 (1:200, 60186-1-Ig, Proteintech), anti-c-Myc (1:200, 10828-1-AP, Proteintech) and anti-E-cadherin (1:400, 20874-1-AP, Proteintech) antibodies using the method described before25. IHC results were evaluated by two independent pathologists, according to both the staining intensity and percentage of positively stained cells.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin-embedded specimens were cut into 5-μm sections, followed by IHC staining with anti-TBL1XR1 (1:400, HPA019182, Sigma), anti-Cyclin-D1 (1:200, 60186-1-Ig, Proteintech), anti-c-Myc (1:200, 10828-1-AP, Proteintech) and anti-E-cadherin (1:400, 20874-1-AP, Proteintech) antibodies using the method described before25. IHC results were evaluated by two independent pathologists, according to both the staining intensity and percentage of positively stained cells.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of PPA1 on cell viability was determined by MTT assay using tetrazolium 3-[4,5]-dimethylthiahiazo(-z-y1)-3,5-di-phenytetrazoliumromide dye (Guo et al 2015). Briefly, transfected cells were seeded into a 96-well plate (4 × 10 3 /well) and allowed for adhesion overnight.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The following articles were also excluded: three duplicated publications (Zhou et al, 2007b;Zhou et al, 2010a;Yang et al, 2014); three without data for HR and 95%CI calculations and adequate contact with the investigators could not be established (Natrajan et al, 2006;Mao et al, 2008;Hanada et al, 2013); two with a sample size<50 (Hsu et al, 2012;Tao et al, 2014); two in which HDGF expression was not detected by IHC methods (Savola et al, 2009;Zhang et al, 2010); three uncorrelated. Finally, 26 cohort studies were found eligible for the meta-analysis (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Lin et al, 2012;Han et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Zhang et al, 2014), containing 32 datasets (29 datasets for OS; 17 datasets for DFS) were qualified to the standard of the meta-analysis. The main characteristics of the selected studies were summari...…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…In recent years, elevated levels of hepatoma-derived growth factor (HDGF) have been observed in a variety of malignancies and high levels of HDGF appears to be associated with increased malignancy across cancers, as witnessed by the correlation with adverse characteristics such as poor patient survival (Hu et al, 2003;Ren et al, 2004;Iwasaki et al, 2005;Uyama et al, 2006;Yamamoto et al, 2006;Yoshida et al, 2006;Chang et al, 2007;Yamamoto et al, 2007;Zhou et al, 2007a;Hu et al, 2009;Savola et al, 2009;Zhang et al, 2010;Zhou et al, 2010b;Liu et al, 2011;Wang et al, 2011;Ye et al, 2011;Zhang et al, 2011;Chen et al, 2012a;Chen et al, 2012b;Hsu et al, 2012;Lin et al, 2012;Han et al, 2013;Hanada et al, 2013;Li et al, 2013a;Li et al, 2013b;Li et al, 2013c;Yang et al, 2013;Guo et al, 2014b;Song et al, 2014;Wang et al, 2014;Yang et al, 2014;Zhang et al, 2014). As a multifunctional protein Bao et al, 2014) widely expressed by many types of human cells, HDGF is involved in the regulations of a myriad of cancer cell activities during cancer transformation (Yang et al, 2013), apoptosis , angiogenesis (Ren et al, 2009), and metastasis (Chen et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%